2016
DOI: 10.1111/jphd.12141
|View full text |Cite
|
Sign up to set email alerts
|

Cost‐effectiveness of preventing dental caries and full mouth dental reconstructions among Alaska Native children in the Yukon–Kuskokwim delta region of Alaska

Abstract: Objective We conducted a cost-effectiveness analysis of five specific dental interventions to help guide resource allocation. Methods We developed a spreadsheet-based tool, from the healthcare payer perspective, to evaluate the cost effectiveness of specific dental interventions that are currently used among Alaska Native children (6-60 months). Interventions included: water fluoridation, dental sealants, fluoride varnish, tooth brushing with fluoride toothpaste, and conducting initial dental exams on childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 18 publications
2
43
0
1
Order By: Relevance
“…Our findings were consistent with a study that showed biannual fluoride varnish applications are more expensive and more effective than current practice . Other studies have shown that the intervention is cost‐saving for children under 6 years . A possible reason for cost savings among young children is that the intervention was compared to the costs of subsequent dental treatments that are often performed under general anaesthesia.…”
Section: Discussionsupporting
confidence: 90%
“…Our findings were consistent with a study that showed biannual fluoride varnish applications are more expensive and more effective than current practice . Other studies have shown that the intervention is cost‐saving for children under 6 years . A possible reason for cost savings among young children is that the intervention was compared to the costs of subsequent dental treatments that are often performed under general anaesthesia.…”
Section: Discussionsupporting
confidence: 90%
“…Evidence‐based clinical practices already proven to be effective in controlling dental caries and recommended by leading national authoritative bodies are already being used, but need to be consistently provided. Such guidelines should include (i) an annual oral health assess‐and‐treat campaign to assess dental needs and provide follow‐on care to stop the decay activity of all children in the villages; (ii) a daily fluoride toothbrushing programme at school‐like settings to promote oral health; and (iii) a semiannual or more frequent professional application of topical fluoride to prevent tooth decay …”
Section: Discussionmentioning
confidence: 99%
“…Such guidelines should include (i) an annual oral health assess-andtreat campaign to assess dental needs 34,36 and provide follow-on care to stop the decay activity of all children in the villages; [37][38][39][40][41] (ii) a daily fluoride toothbrushing programme at school-like settings to promote oral health; 42,43 and (iii) a semiannual or more frequent professional application of topical fluoride to prevent tooth decay. [44][45][46] With respect to quality improvement in a complex setting, the literature suggests that distribution of new guidelines will not be sufficient to improve care delivery.…”
Section: Discussionmentioning
confidence: 99%
“…For example, US settler colonial practices introduced sugar into indigenous communities, and sugar‐sweetened foods and beverages are now among the most commonly consumed items in Alaska Native Communities . Furthermore, Alaska Native Communities are small, geographically isolated and situated on permafrost, making the cost of piped fluoridated water prohibitive . Complicating local acceptance of water fluoridation is the only documented death due to insufficient monitoring of water fluoridation, which occurred in the 1990s in an Alaska Native Community .…”
Section: Introductionmentioning
confidence: 99%